2017
DOI: 10.1088/1361-6528/aa7f34
|View full text |Cite
|
Sign up to set email alerts
|

The Joule heating problem in silver nanowire transparent electrodes

Abstract: Silver nanowire transparent electrodes have shown considerable potential to replace conventional transparent conductive materials. However, in this report we show that Joule heating is a unique and serious problem with these electrodes. When conducting current densities encountered in organic solar cells, the average surface temperature of indium tin oxide (ITO) and silver nanowire electrodes, both with sheet resistances of 60 ohms/square, remains below 35 °C. However, in contrast to ITO, the temperature in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 55 publications
1
68
0
2
Order By: Relevance
“…While the first category is supposed to heat homogeneously the whole TH surface, the second category can induce local heating due to its nonhomogeneous nature, if heat does not diffuse along both the active material and/or the substrate quickly enough. [ 54 ] These hotspots can induce local degradation within the TH and are therefore an issue to be dealt with. Das et al investigated scaling in self‐heated percolating networks and concluded that hotspot clustering appears to be a mechanism analogous to crystallization physics.…”
Section: Principle Of Thsmentioning
confidence: 99%
See 4 more Smart Citations
“…While the first category is supposed to heat homogeneously the whole TH surface, the second category can induce local heating due to its nonhomogeneous nature, if heat does not diffuse along both the active material and/or the substrate quickly enough. [ 54 ] These hotspots can induce local degradation within the TH and are therefore an issue to be dealt with. Das et al investigated scaling in self‐heated percolating networks and concluded that hotspot clustering appears to be a mechanism analogous to crystallization physics.…”
Section: Principle Of Thsmentioning
confidence: 99%
“…This roughly corresponds to an area with more than one hundred nanowires. [ 54 ] A comparable technique used to reveal defects in microelectronic devices is lock‐in thermography (LiT). [ 105 ] It can provide an IR emission intensity and a heat timing map [ 106 ] but does not include any thermal calibration or numerical scale.…”
Section: Principle Of Thsmentioning
confidence: 99%
See 3 more Smart Citations